Prospects Business Development Eating Rice Ramas Rumble 6000 In the city of Pekanbaru - Febrialfet ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Development of small industries in the national economy has a role in trying toensure equal distribution of opportunities, and equal employment expansion and increasedrevenue. One of the small industries that experienced considerable improvement in the city ofPekanbaru Riau Province is home Eat Rice Industry Ramas Rumble 6000. Based on thebackground of the existing formulation of the problem and this research aims tomengetahuiprospek of development Eating Rice Ramas Rumble 6000. The population in thisstudy is the 6000 all-round restaurant in the city of Pekanbaru, at which time the study wasrecorded 15 units usahadengan total sample of 15 business units.The data was collected using interviews and observations in the field. The dataobtained were used to determine the feasibility of the 6000 all-ramas rice tobe developed in the city of Pekanbaru.The results explain that the restaurant business all-round rice ramas 6000 is eligible tobe developed in the city of Pekanbaru to absorb labor in order to reduce unemployment in thecity of Pekanbaru., Growth or an increase in the restaurant business all-round rice ramas 6000driven by the availability of raw materials in market and price stability dipasaran.Faktor thatinfluence the development of eating rice ramas home business 6000 is the all-rounddevelopment of the city of Pekanbaru in various aspects of development. In terms of revenuecontribution, ramas rice restaurant business department was able to obtain Net 6000 B / Cratio above 1 and able to provide employment for people in the city of Pekanbaru. Meanwhile,the problems faced was the unavailability of support tools for the average transportationemployers use the services of a car rental for the purposes of deliveries for events.Keywords: